Distribution of stream macroalgal communities from the mid-western region of Paraná state, southern Brazil: importance of local scale variation - Branco, Ciro Cesar Zanini [UNESP]; Krupek, Rogério Antônio [UNESP]; Peres, Cleto Kaveski [UNESP] (Brazilian Archives of Biology and Technology, 2009)
Durante o período de maio a outubro de 2002, vinte e dois segmentos de riachos, representando os diversos tipos de ambientes da região centro-oeste do estado do Paraná, sul do Brasil, foram amostrados quanto à comunidade de macroalgas. Foram encontradas vinte e sete macroalgas. A divisão Chlorophyta foi o grupo algal predominante, seguido por Cyanobacteria, Rhodophyta e Chrysophyta. A espécie com melhor distribuição foi Phormidium retzii. Foi observado um padrão de distribuição em mosaico. O número de espécies por ponto de amostragem variou de zero a seis e correlacionou-se positivamente com abundância de espécies. Por outro lado, nenhuma outra correlação significativa foi encontrada entre número de espécies e abundância com as variáveis ambientais. Os resultados, suportados por dados de literatura, indicaram uma variação ampla e aleatória entre os riachos, sugerindo que a distribuição da comunidade de macroalgas na área de estudos parece responder mais fortemente a variações nas condições em escala local do que em escalas regionais maiores.

Twenty-two stream segments, representing the diverse types of environments in the mid-western region of the Paraná State, southern Brazil, were sampled for occurrence of macroalgal communities from May to October in 2002. Twenty-seven macroalgal taxa were found, with Chlorophyta as the dominant algal group, followed by Cyanobacteria, Rhodophyta and Chrysophyta. The most widespread species was Phormidium retzii. Distribution was patchy, with species number per sampling sites ranging from zero to six and correlated positively with the abundance. on the other hand, no significant correlation was found among the species number and abundance with environmental variables. Results indicated wide and random variation among the streams. Thus, it seemed that the distribution of macroalgal communities in the study area responded more closely to the local-scale variation than the regional characteristics.
Keywords: local-scale variation; Paraná State; stream macroalgae; restricted distribution; Brazil